Cartilla de Entrenamiento Virtual. “Cuerpo y Expresión” Nivel básico, para Para adolescentes entre 12 a 15 años (2021)
This thesis has as a final product a digital basic training booklet for students between 12 and 15 years of age, which arises from the experience of the virtual pedagogical practice 2020-2, through that period, attenuation was evidenced in the students of some bodily capacities due to confinement due to health problems as a result of the Covid-19 pandemic.